2019
DOI: 10.1186/s12915-019-0701-1
|View full text |Cite
|
Sign up to set email alerts
|

GLIPR1L1 is an IZUMO-binding protein required for optimal fertilization in the mouse

Abstract: BackgroundThe sperm protein IZUMO1 (Izumo sperm-egg fusion 1) and its recently identified binding partner on the oolemma, IZUMO1R, are among the first ligand-receptor pairs shown to be essential for gamete recognition and adhesion. However, the IZUMO1-IZUMO1R interaction does not appear to be directly responsible for promoting the fusion of the gamete membranes, suggesting that this critical phase of the fertilization cascade requires the concerted action of alternative fusogenic machinery. It has therefore be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 68 publications
0
22
1
Order By: Relevance
“…These genes were zona pellucida binding protein ( ZPBP ) and regulated endocrine specific protein 18 ( RESP18 ) in hypermethylated group and glioma pathogenesis‐related 1‐like protein 1 ( GLIPR1L1 ) in hypomethylated group. Previous studies clearly demonstrated the significant role of GLIPR1L1 in sperm‐oocyte binding in mice and bovine (Caballero et al, 2012; Gaikwad et al, 2019; Gibbs et al, 2010). Furthermore, mice lacking ZPBP genes produced abnormal sperm cells with decreased ability to penetrate zona pellucida (Lin et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…These genes were zona pellucida binding protein ( ZPBP ) and regulated endocrine specific protein 18 ( RESP18 ) in hypermethylated group and glioma pathogenesis‐related 1‐like protein 1 ( GLIPR1L1 ) in hypomethylated group. Previous studies clearly demonstrated the significant role of GLIPR1L1 in sperm‐oocyte binding in mice and bovine (Caballero et al, 2012; Gaikwad et al, 2019; Gibbs et al, 2010). Furthermore, mice lacking ZPBP genes produced abnormal sperm cells with decreased ability to penetrate zona pellucida (Lin et al, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, we detected IZUMO1, IZUMO2, and IZUMO4, and interestingly, the most important reported proteins responsible for fertilization were unaffected during the vitrification process, unlike with the slow-freezing method. Recently, GLIPR1-like protein 1 (GLIPRL1L1) was identified in the spermatozoa, and loss of this protein results in failure of IZUMO1 relocalization to fuse with eggs (Gaikwad et al, 2019). We also identified GLIPRL1L1 in human spermatozoa and found that the protein was unaffected during the vitrification process.…”
Section: Effect Of Spermatozoa Vitrification On Functional Spermatozoa Proteins Responsible For Participation In Spermatozoa-oocyte Intermentioning
confidence: 83%
“…This, and the mismatch in the CRISP2 localization and null sperm phenotype data, suggests that other as yet unknown CRISP receptors exist on sperm. The identity of these receptors, and the possibility that CAP domain receptors may also exist on sperm, as indicated by the role of non-CRISP CAP proteins on sperm function ( Gaikwad et al, 2019 ), is the subject of ongoing research.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these ion channels, including CatSper1 ( Vicens et al, 2014b ) and TRPM8 ( Majhi et al, 2015 ), have also experienced positive selection. In addition, the CAP domains, including those in CRISPs, are proposed to have roles in sperm-oocyte fusion ( Yamaguchi et al, 2011 ; Ernesto et al, 2015 ; Gaikwad et al, 2019 ). These data suggest that the recruitment of an ICR domain onto an ancestral CAP domain, and hinge region, during evolution to form the founding CRISP gene in vertebrates, then their subsequent expansion and over expression within the mammalian male reproductive tract ( Abraham and Chandler, 2017 ), represents an example of positive Darwinian evolution driven by the combined ability of CRISPs to boost sperm motility and assist in oocyte binding.…”
Section: Discussionmentioning
confidence: 99%